Best Answer

x3 - 3x2 + 4

Since the coefficients of the odd powers of x (=1) is the same as the sum of the even powers (-3+4=1), then x = -1 must be a root. That is to say, (x + 1) is a factor.

So you can rewrite the expression as

x3 + x2 - 4x2 - 4x + 4x + 4

= x2(x + 1) - 4(x + 1) + 4(x + 1)

= (x + 1)*(x2 - 4x + 4)

= (x + 1)*(x - 2)2

Q: How do you factor x3-3x2 plus 4?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

a2 - 4a + 4

(2x+4)(x+1)

(3x + 4)(3x + 4)

That's 44v + 4 which factors to 4(11v + 1)

(b + 4)(b + 4)

Related questions

Not factorable

(2x + 1)(x + 4)

a2 - 4a + 4

(2x+4)(x+1)

(3x + 4)(3x + 4)

4(x + 1)(x + 1)

(x+1)(x+4)

(x-1)(x+4)

That's 44v + 4 which factors to 4(11v + 1)

x3 + x2 + 4x + 4 = (x2 + 4)(x + 1)

x3 + 4x2 + x + 4 = (x + 4)(x2 + 1)

(b + 4)(b + 4)